A facile route to mechanically robust graphene oxide fibers. Issue 35 (28th June 2019) - Kwon, Youbin; Lee, Byoung-Sun; Park, Sarang; Yu, Woong-Ryeol
Abstract : Excellent mechanical, electrical, and thermal properties of graphene have been achieved at the macroscale by assembling individual graphene or graphene oxide (GO) particles. Abstract : Excellent mechanical, electrical, and thermal properties of graphene have been achieved at the macroscale by assembling individual graphene or graphene oxide (GO) particles. Wet-spinning is an efficient and well-established process that can provide GO assemblies in fiber form. The coagulation bath in the wet-spinning process has rarely been considered for the design of mechanically robust GO fibers (GOFs). In this study, locating the amidation reaction in the coagulation bath yielded mechanically improved GOFs. The imides 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide and N -hydroxysuccinimide were used to form covalent amide bonds between GO flakes and chitosan, thereby reinforcing the GOFs. Evidence and effects of the amidation reaction were systematically examined. The tensile strength and breaking strain of the GOFs improved by 41.6% and 75.2%, respectively, and the toughness almost doubled because of the optimized crosslinking reaction. Our work demonstrated that using a coagulation bath is a facile way to enhance the mechanical properties of GOFs.